Linguistic Traits and Human Capital Formation - Oded Galor; Ömer Özak; Assaf Sarid (Institute of Labor Economics (IZA), 2020)
This research establishes the influence of linguistic traits on human behavior. Exploiting variations in the languages spoken by children of migrants with identical ancestral countries of origin, the analysis indicates that the presence of periphrastic future tense, and its association with long-term orientation has a significant positive impact on educational attainment, whereas the presence of sex-based grammatical gender, and its association with gender bias, has a significant adverse impact on female educational attainment.
Keywords: D91; I25; J16; J24; Z10; Z13; 330; human capital; long-term orientation; gender bias; periphrastic future tense; sex-based grammatical gender; culture; language